Qur’anic Literacy within the Framework of Cultural Da’wah as a Model for Islamic Community Development (Empower : Jurnal Pengembangan Masyarakat Islam, 2026)
Many elderly individuals continue to struggle to read the Qur’an fluently, a challenge further exacerbated by inadequate learning facilities. However, within the Griya Mijen Permai Housing Complex, there is a Qur’an learning community that serves as a center for parents and the elderly. This community has succeeded in assisting numerous elderly learners, transforming their inability to read the Qur’an into the ability to read it proficiently. This study aims to examine the stages, strategies, and outcomes of the learning activities implemented by the Qur’an Community for Parents and the Elderly in Griya Mijen Permai, Semarang City. The research employed a qualitative-descriptive method. Data were collected through interviews, observations, and documentation. The findings indicate three key aspects. First, in terms of stages, the learning process includes preparation (formation and socialization), planning (setting objectives, selecting methods and strategies), implementation (providing motivation, delivering instruction, and note-taking), and evaluation conducted by an appointed examiner. Second, the strategies encompass scheduling, group division, the use of the Iqra’ method, the application of the traditional sorogan technique, savings and donations, venue rotation, provision of refreshments, and recreational activities. Third, the outcomes demonstrate significant improvements in participants’ Qur’an reading abilities, strengthened social bonds among members, and increased community trust, as evidenced by their active roles in various community events such as halalbihalal gatherings and Indonesian Independence Day celebrations.